PENGARUH MODEL PEMBELAJARAN TERPADU TERHADAP HASIL BELAJAR IPA - Nurul Fazriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2016)
This study aimed to determine the effect of integrated learning model toward science learning outcomes. The study was conducted in SDN Kemiri Muka 1 Depok in fifth grade school year 2014/2015 using cluster random sampling was done to 80 students. Retrieval of data obtained through tests and analyzed using Analysis of Variance (ANOVA) and two lines with the design treatment by level 2x2. The results showed that science learning outcomes that given thematic learning model integrated model of integrative is higher than in the group of students given fragmented learning model. The results of this study indicate that the thematic learning model integrated can improve science learning outcomes of students. Keywords : Learning Outcomes Ipa, Model Integrated Learning, Learning Thematic